2019
DOI: 10.1103/physrevb.99.085426
|View full text |Cite
|
Sign up to set email alerts
|

Boundaries of boundaries: A systematic approach to lattice models with solvable boundary states of arbitrary codimension

Abstract: We present a generic and systematic approach for constructing D−dimensional lattice models with exactly solvable d−dimensional boundary states localized to corners, edges, hinges and surfaces. These solvable models represent a class of "sweet spots" in the space of possible tight-binding models-the exact solutions remain valid for any tight-binding parameters as long as they obey simple locality conditions that are manifest in the underlying lattice structure. Consequently, our models capture the physics of bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 74 publications
0
45
0
Order By: Relevance
“…where a † A,m,m creates a state on the A sublattice (red in Fig. 1(a)) in the unitcell numbered by (m, m ) starting with (0, 0) at the lower left corner [17,28]. In addition to the corner localisation, a second striking feature of this state is that it resides on the (red) A sublattice.…”
Section: Breathing Kagome Lattice Of Lightmentioning
confidence: 98%
“…where a † A,m,m creates a state on the A sublattice (red in Fig. 1(a)) in the unitcell numbered by (m, m ) starting with (0, 0) at the lower left corner [17,28]. In addition to the corner localisation, a second striking feature of this state is that it resides on the (red) A sublattice.…”
Section: Breathing Kagome Lattice Of Lightmentioning
confidence: 98%
“…Remarkably, these models host zero-dimensional corner modes under the open boundary conditions in all directions, which coincide with the quantization of the bulk multipole moment under the periodic boundary conditions. This kind of HOTI states was also found in breathing kagome and pyrochlore lattices [22][23][24][25]. Together with these theoretical developments, experimental realization of the HOTIs has also been intensively pursued both in solid-state systems [26] and artificial materials [27][28][29][30].…”
mentioning
confidence: 96%
“…Since the adiabatic connection to the irreducible cluster state is a ubiquitous property of the SPT phases, the characterization of the HOSPT phases by the Z Q Berry phase can applicable to wide class of models beyond the square-lattice models, such as the breathing kagome/pyrochlore models [44,51] Recently, it is found that the breathing kagome model and breathing Pyrochlore model have the higher-order topological insulator (HOTI) phase [22,24]. In the HOTI phases, the models have mid-gap corner states, which is exactly solvable with certain boundary conditions [23,25]. In this section, we show the correspondence between the Z Q Berry phases and the HOTI phases in the breathing kagome model and the breathing Pyrochlore model.…”
mentioning
confidence: 99%
“…From Eqs. (33) and (34), one finds that the energy eigenvalue ε L (k y ) has to be determined such that…”
Section: Dispersion Relation Of Edge Modementioning
confidence: 99%